ANALISIS PENGARUH KINERJA GURU PENDIDIKAN AGAMA ISLAM (PAI) DI SMK ISLAM YAPIM KOTA MANADO - Abdul Latif Samal; Nasruddin Yusuf; Rivai Bolotio (Edukasi Islami : Jurnal Pendidikan Islam, 2021)
This study attempted to reveal: a) the performance of Islamic education teachers at SMK Islam Yapim Manado City, b) SMK Islam Yapim Manado City students’ learning motivation, and c) contribution size of teachers’ performance to SMK Islam Yapim Manadoo City students’ learning motivation.Research population is all the students of SMK Islam Yapim Manado City. Sampling using random cluster sampling. The data collecting using closed list quesionare. Data respondent is students. The validity testing of instruments using construct validity. The reliability testing of instruments is done with internal consistency testing with Cronbach Alpha technique. The data analysis technique includes descriptive and inferensial analysis. The inferensial analysis using partial correlation and regression. All the analysis using SPSS program forWindows.Based on the descriptive analysis results can be known that the performance of Islamic education teachers at SMK Islam Yapim Manado City good category (61.5%). While the SMK Islam Yapim Manado City students’ learning motivation of Islamic education teacher generally in the high category (48.5%). Based on the results of regression analysis found determinan coefficients (R2) = 0.353. Test results of F obtaining the value of F = 13.508 (sig = 0.000